Exploring the Daily Life of Mining Communities: The Case of Antofagasta, Chile - Mayol-Miranda, A; Azocar-Ortiz, C (Routledge, 2019)
Social sciences have documented the economic and social impacts of mining activities on communities around the world, showing mining towns and villages, on the one hand, present high economic growth and, on the other, have problematic quality-of-life indicators. In this article, we present the results of an extensive ethnographic study of one city in northern Chile, Antofagasta, located in a region where about half of the country s total copper production is concentrated. We sociologically explore these trends and document how they are interconnected and configure specific ways of living and inhabiting a place. Far from disproving the problematic relationship between social development and the mining industry, we reflect on the interrelatedness of the impacts of mining projects and suggest analytical clues for an ecological study of mining cities. © 2019, © 2019 Informa UK Limited, trading as Taylor & Francis Group.